Thermoregulated Nitric Cryosystem for Cooling Gas-Filled Detectors of Ionizing Radiation - Zharkov, I.P.; Kutniy, V.Ye.; Rybka, A.V.; Palamarchuk, S.P.; Safronov, V.V.; Selivanov, O.V.; Solonetsky, A.G.; Khodunov, V.O.; Kholomeev, G.O. (Science and Innovation, 2024)
A cryosystem has been designed for cooling and filling the gas-filled detectors of ionizing radiation with compressed inert gas. It is based wide-mouthed nitrogen cryostat that enables controlling detector temperature in the range of 173 – 293 K and stabilizing it with accuracy of ± 1°. The project has been implemented within the Ukraine–NATO Program of Collaboration, Grant SfP no.984655.